Cadaveric bone marrow mesenchymal stem cells: first experience treating a patient with large severe burns. Issue 1 (December 2015) - Mansilla, Eduardo; Marín, Gustavo; Berges, Mirta; Scafatti, Silvia; Rivas, Jaime; Núñez, Andrea; Menvielle, Martin; Lamonega, Roberto; Gardiner, Cecilia; Drago, Hugo; Sturla, Flavio; Portas, Mercedes; et al.
Abstract Background In January 2005, Rasulov et al. originally published "First experience in the use of bone marrow mesenchymal stem cells (MSCs) for the treatment of a patient with deep skin burns". Here, we present the first ever treated patient with cadaveric bone marrow mesenchymal stem cells (CMSCs) in the history of Medicine. Methods A young man, who severely burned 60 % of his total body surface with 30 % of full-thickness burns while working with a grass trimmer that exploded, was involved in the study. MSCs were obtained from the bone marrow of a cadaver donor in a routine procurement procedure of CUCAIBA, the Province of Buenos Aires, Argentina, Ministry of Health, Transplantation Agency, cultured, expanded, and applied on the burned surfaces using a fibrin spray after early escharotomy. Results So far, our preliminary experience and our early results have been very impressive showing an outstanding safety data as well as some impressive good results in the use of CMSCs. Conclusions Based on all this, we think that improvements in the use of stem cells for burns might be possible in the near future and a lot of time as well as many lives could be saved by many other research teams all over the world. CMSCs will probably be a real scientific opportunity in Regenerative Medicine as well as in Transplantation.